Investigating of EFL Teachers’ Ability in Creating Innovative Instructional Design: (Qualitative Descriptive Research at SMAN 04 Kaur) - Suhada, Ajis (Universitas Bengkulu, 2024)
This research aims to investigate the ability of English as a Foreign Language (EFL) teachers in creating innovative learning designs at State High School (SMAN) 04 Kaur. This research uses a descriptive qualitative approach to understand in depth the ability of teachers to design and implement innovative learning designs in the context of English learning. This research involves collecting data through classroom observations, interviews with teachers, and analysis of learning documents. The results of this research provide insight into the challenges, potential and strategies used by EFL teachers in creating innovative learning designs. It is hoped that the findings of this research can make an important contribution in improving the quality of English learning at SMAN 04 Kaur, as well as being a guide for other EFL teachers who want to improve their abilities in creating innovative learning designs. Keywords: EFL Teacher, Innovative Learning Design, English Learning